Gaya Belajar Siswa Berprestasi - Lita Nurbaiti; Padyah Padyah; Nanda Oktaviani Muzakia (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
In this study the predominance of learning styles on high-achieving students in learning activities in Pondok Bahar State Elementary School 06 2019 school year is auditory learning style. students use visual learning styles with the characteristics that emerge namely: high tone of voice when speaking, pay attention to one's lips movements when invited to speak, feel disturbed if the atmosphere of KBM is crowded, have difficulty remembering verbal explanations, always noting every teacher's explanation, being very careful in writing , and can always solve problems if you read first; as much as students use auditory learning styles with the characteristics that emerge namely tilted their heads to answer oral questions, lazy to take notes, when writing writing is not neat, can not read silently, recite what will be remembered, active in group discussions, happy to talk, lazy if asked to read, lazy if asked to do writing assignments, bored with reading that is too long.